Variations in Postpartum Hemoglobin Values in Maternal Patients Residing at High Altitude - Jhofre Vinicio Prado Quilambaqui; Ximena Elizabeth Trujillo Romero; Olga Cristina Solis Solis (Medisur)
Foundation: hemoglobin disorders can have a significant impact on maternal well-being and fetal development, for this reason, they constitute a critical indicator. Objective: to identify variations in hemoglobin values after childbirth in patients living at high altitude who were treated in a hospital in the Sierra region of Ecuador. Method: a descriptive cross-sectional study was carried out on patients treated at a health center in the province of Tungurahua, belonging to a hospital in the Ecuadorian mountains between January and December 2022. The sample consisted of 124 patients. The Kolmogorov-Smirnov test and Wilcoxon signed rank test were used. Results: 55.6 % of the pregnant women were under 30 years of age, 61.3 % were married and 71.8 % of the pregnancies were unplanned. Before delivery, the mean value of maternal hemoglobin was 11.736 g/dl, while after delivery it was 10.927 g/dl, a figure that showed a statistically significant variation (Z = -9.557; p < 0.001). Conclusions: hemoglobin values during the third trimester of pregnancy experience a significant decrease after delivery, which persists after 45 days.